THE ANALYSIS OF TERRITORIAL IDENTITY IN NOVOSIBIRSK - Pirotskaya, A.V. (Perm Federal Research Centre Journal, 2015)
This article proposes the analysis of territorial identity in the city of Novosibirsk and the Novosibirsk region. The analysis was conducted on the basis of previous studies in the field of urban sociology, also conducted by the author. The main focus of this research was to study the perception of the different zones in the city, as well as the perception of its boundaries. The author draws attention to the specificity of this region in the context of territorial identity.